Astrobiology as a framework for investigating antibiotic susceptibility: a study of Halomonas hydrothermalis. Issue 126 (31st January 2017) - Harrison, Jesse P.; Angel, Roey; Cockell, Charles S.
Abstract : Physical and chemical boundaries for microbial multiplication on Earth are strongly influenced by interactions between environmental extremes. However, little is known about how interactions between multiple stress parameters affect the sensitivity of microorganisms to antibiotics. Here, we assessed how 12 distinct permutations of salinity, availability of an essential nutrient (iron) and atmospheric composition (aerobic or microaerobic) affect the susceptibility of a polyextremotolerant bacterium, Halomonas hydrothermalis, to ampicillin, kanamycin and ofloxacin. While salinity had a significant impact on sensitivity to all three antibiotics (as shown by turbidimetric analyses), the nature of this impact was modified by iron availability and the ambient gas composition, with differing effects observed for each compound. These two parameters were found to be of particular importance when considered in combination and, in the case of ampicillin, had a stronger combined influence on antibiotic tolerance than salinity. Our data show how investigating microbial responses to multiple extremes, which are more representative of natural habitats than single extremes, can improve our understanding of the effects of antimicrobial compounds and suggest how studies of habitability, motivated by the desire to map the limits of life, can be used to systematically assess the effectiveness of antibiotics.